First Geodetic Observations Using New VLBI Stations ASKAP-29 and WARK12M - Petrov, L.; Phillips, C.; Tzioumis, T.; Stansby, Bruce; Reynolds, Cormac; Bignall, Hayley; Gulyaev, S.; Natusch, T.; Palmer, N.; Collett, D.; Reynolds, J.; Amy, S.; et al. (CSIRO, 2011)
We report the results of a successful 7-hour 1.4 GHz Very Long Baseline Interferometry (VLBI) experiment using two new stations, ASKAP-29 located in Western Australia and WARK12M located on the North Island of New Zealand. This was the first geodetic VLBI observing session with the participation of these new stations. We have determined the positions of ASKAP-29 and WARK12M. Random errors on position estimates are 150–200mm for the vertical component and 40–50mm for the horizontal component. Systematic errors caused by the unmodeled ionosphere path delay may reach 1.3mfor the vertical component.